The influence of salivary pH on the adhesion of Candida albicans to acrylic prosthetic materials obtained using conventional and digital techniques - Hanan Al-Otaibi; Aseel Alomair; Latifa AlSewailem; Rana AlFadhel; Sarah Bin Durayhim; Fatimah Al-Otibi; Raedah Alharbi; Afnan Alfouzan; Sara Al Taweel; Huda Alshehri; Nawaf Labban (Polimery)
The influence of saliva pH on the adhesion of Candida albicans to PMMA-based prosthetic ma-terials manufactured using conventional and digital techniques (3D printing, milling) was examined. The obtained data were subjected to statistical analysis using one-way ANOVA and the Tukey HSD post hoc test (α = 0.05). Materials obtained by 3D printing had the highest surface roughness, while those ob-tained conventionally had the highest number of CFU (colony-forming unit). The mean CFU value was highest at pH 4.5 and statistically significant compared to other pH values. No significant correlation was found between surface roughness and the average CFU value. The surface of materials obtained using the conventional and milling methods showed lower adhesion of Candida albicans.